What does it mean to be an ‘international’ journal?: What is submitted to TLI is what shapes TLI - Chick, Nancy; Mårtensson, Katarina (Teaching and Learning Inquiry, 2020)
An introduction to volume 8, issue 1 of Teaching & Learning Inquiry.